IMF Staff papers : Volume 2 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1952)
This paper focuses on the relation of inflation to economic development. Due to the inadequacy of savings and the difficulty of directing them into productive investment, there is a strong temptation to raise the level of investment by expanding bank credit-that is, by inflation. In most low-income countries, even the most forceful measures for increasing savings and for applying them to the most urgent needs would still leave the economy with inadequate resources for the investment necessary to assure tolerable progress in raising productive efficiency and expanding production. The only way of securing adequate resources for development in such countries is by supplementing domestic savings with capital from abroad. It is characteristic of the underdeveloped countries that the resources they put into investment are generally a smaller proportion of their very much smaller national product than is true for the more highly developed countries. The proportionally low level of investment in underdeveloped countries may be due to various factors. Frequently, though not universally, the cause of inadequate investment is the unavailability of savings.